ECPR2: Expert Consensus on PeRcutaneous Cannulation for Extracorporeal CardioPulmonary Resuscitation. (October 2022) - Schmitzberger, Florian F.; Haas, Nathan L.; Coute, Ryan A.; Bartos, Jason; Hackmann, Amy; Haft, Jonathan W.; Hsu, Cindy H.; Hutin, Alice; Lamhaut, Lionel; Marinaro, Jon; Nagao, Ken; Nakashima, Takahiro; et al.
Abstract: Aim: Extracorporeal cardiopulmonary resuscitation (ECPR) has emerged as a promising resuscitation strategy for select patients suffering from refractory out-of-hospital cardiac arrest (OHCA), though limited data exist regarding the best practices for ECPR initiation after OHCA. Methods: We utilized a modified Delphi process consisting of two survey rounds and a virtual consensus meeting to systematically identify detailed best practices for ECPR initiation following adult non-traumatic OHCA. A modified Delphi process builds content validity and is an accepted method to develop consensus by eliciting expert opinions through multiple rounds of questionnaires. Consensus was achieved when items reached a high level of agreement, defined as greater than 80% responses for a particular item rated a 4 or 5 on a 5-point Likert scale. Results: Snowball sampling generated a panel of 14 content experts, composed of physicians from four continents and five primary specialties. Seven existing institutional protocols for ECPR cannulation following OHCA were identified and merged into a single comprehensive list of 207 items. The panel reached consensus on 101 items meeting final criteria for inclusion: Prior to Patient Arrival (13 items), Inclusion Criteria (8), Exclusion Criteria (7), Patient Arrival (8), ECPR Cannulation (21), Go On Pump (18), and Post-Cannulation (26). Conclusion: We present a list of items for ECPR initiation following adult nontraumatic OHCA, generated using a modified Delphi process from an international panel of content experts. These findings may benefit centers currently performing ECPR in quality assurance and serve as a template for new ECPR programs.